(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Several immunoassays are currently used to measure humoral immunity to the rabies virus. A standard or reference serum is a consistent component of all assays to standardize the results and control the assay performance. Two human international standard rabies immune globulin (SRIG) reference serum preparations are recognized by the World Health Organization (WHO): the first international WHO SRIG(WHO 1) with a potency of 59 IU and the second WHO SRIG(WHO 2) with a potency of 30 IU. The WHO 1 SRIG is also known as RIG Lot R-3 in the United States, distributed by Center for Biologics Evaluation and Research (CBER). The WHO 2 SRIG is distributed by National Institute for Biological Standards and Control (NIBSC) in the UK. These standards are used globally to promote uniform potency measurement of RIG products used for prophylaxis, individual vaccine response, and disease diagnosis in a standard international unit (IU/mL). Because it is important to have consistent and accurate assignment of IU/mL values for rabies immune globulin (RIG) products and reliable vaccine response measurements for the evaluation of vaccines, the SRIG in use for a particular method should be routinely evaluated for potency against a recognized international standard. Previous studies in 1997 and 2006 have indicated that WHO 1 SRIG has lost potency in comparison with WHO 2 SRIG. Further potency comparison studies have supported this finding. To determine the difference in potency between the two SRIG preparations and their potencies in different assays, a comparison study was performed at KSU. Three potency levels of each SRIG and four rabies virus neutralizing antibody (RVNA) positive serum samples were tested in two rapid fluorescent focus inhibition assays (RFFIT), differing in challenge virus strain and cell type, and two ELISA assays, one indirect and one blocking. Statistical analysis revealed there is no significant difference overall in the measurements when either WHO 1 or WHO 2 are used as the SRIG in the RFFIT assays. However, a trend was clearly seen in higher IU/ mL values obtained when WHO1 was used as the SRIG to obtain the IU/mL values. Additionally, for some of the samples a significant difference in IU/mL was found. The comparison of indirect ELISA results, where the kit standard is used to calculate the EU/mL values, revealed a significant difference between WHO 1 and WHO 2 measurements at potency level 2.0 IU/mL; with WHO 1 higher in EU/mL value than WHO 2. The potential for obtaining incongruent measurements with use of different SRIG preparation and the performance of each SRIG in different methods should be considered when selecting assays standards/controls and in the interpretation of rabies serology results.